Course on secure hardware design of silicon chips. Issue 4 (18th April 2017) - Halak, Basel
Abstract : This study describes the design and evaluation of a secure chip design module for graduate students and junior engineers with electronics and computer engineering. This course has two broad goals, the first is to teach students how design complex systems on chips using industry standard tools and the second is to educate them on emerging hardware security threats and countermeasures. There are a number of strategies currently been employed to handle the rising complexity of chip design, namely reuse, abstraction and automation. The authors aim to show how to employ these approaches to produce working systems within a time‐constrained environment similar to that of IC design companies. One of the unique features of this module is its approach of treating hardware security as an integral part of the chip design process and as one of the design metrics which can be evaluated and optimised, this allows students to better understand the root causes of this issue and to think more constructively about potential countermeasures. The course is designed based on the principles of constructive alignment method and Kolb learning cycle. Detailed syllabus and assessment exercises are included. Feedback results from students' surveys indicate that the module has been positively received.